Metabolomics and proteomics reveal blocking argininosuccinate synthetase 1 alleviates colitis in mice - Shijia Liu; Haijian Sun; Zijing Du; Shuai Lu; Chenwen Wang; Ye Zhang; Zichen Luo; Lu Wang; Zhimin Fan; Peng Wei; Yujiao Yan; Junzhi Zhang; et al. (Nature Communications)
Abstract To date, treating ulcerative colitis (UC) remains a significant challenge due to its complex etiology. In this study, metabolomics and proteomics analysis for multi-center cohorts reveal that both serum arginine levels and the rate-limiting enzyme argininosuccinate synthetase 1 (ASS1) are significantly elevated in UC patients. Exogenous arginine infusion and ASS1 overexpression exacerbate the pathological features of colitis in mice, while inhibiting or silencing ASS1 offers protection against experimental colitis. The induction of ASS1 is accompanied by increased levels of acetylated H3 and trimethylated H3K4, along with decreased levels of dimethyl H3K9 around the ASS1 promoters, suggesting epigenetic activation of ASS1 in colitis. The ASS1/arginine axis triggers mTOR and iNOS activation and induces gut microbiota dysbiosis, leading to experimental colitis. Additionally, we identify a screened compound, C-01, which significantly improves colitis by highly binding to ASS1. Our findings suggest that ASS1 could be a promising target for UC treatment.